The Auxiliary Role of Artificial Intelligence in the Intelligent Creation and Conducting of Symphony. (14th July 2022) - Dong, Rui
Abstract : In order to improve the effect of symphony intelligent creation and command, this paper combines artificial intelligence technology to study the symphony intelligent creation and command system. Moreover, this paper designs three common signal conditioning circuits, namely gain-adjustable circuit, universal high-order filter, and D/A converter, and implements them in a cross-coupled POTA-based FPAA array. In addition, this paper verifies the programmability and correctness of these three signal conditioning circuits through simulation analysis in cadence software. Finally, this paper builds a simulation system based on the requirements of symphony intelligent creation and conducting. Through the simulation evaluation, it can be seen that the symphony intelligent creation and command system based on artificial intelligence proposed in this paper has a good simulation effect in the symphony intelligent creation and command system, and can play an important role in the symphony intelligent creation and command.